Draft Twelfth Five Year Plan 2012-2017 & Annual Plan 2012-2013 Volume-1 Government of Madhya Pradesh - Planning Commission (Planning Commission, 2012)
On re-organisation of States, The state of Madhya Pradesh was formed on November 1, 1956 as the result of reorganisation of states. The state was bifurcated to form Chhattisgarh State as per the provisions of Madhya Pradesh Reorganisation Act, 2000. Present state of Madhya Pradesh came into existence on 1st November 2000, with 45 districts. Five more districts namely, Alirajpur, Singrauli, Ashoknagar. Burhanpur and Anuppur, were created raising the number of districts in the State to 50.
Government of Madhya Pradesh, Planning, Economics and Statistics Department